Spiritual Origin of Kazakh Folklore (Journal of Oriental Studies, 2018)
One of the main sources of research of the Kazakh philosophy and cultural studies is the study offolklore as the basis of folk wisdom and the form of cultural and philosophical knowledge. The Kazakhfolklore reflects the life, the meaning of existence, the purposes and nation mindset, the world outlookof the people is revealed. Philosophical problems that contained in folklore, help to know the spiritualcontent of national culture and are the methodological basis for cultural, philosophical and scientificconclusions. Accordingly, we can affirm the relevance of this article.The worldview of the people is determined by the degree of development of its spirituality. Thespiritual heritage of the people includes “folk wisdom”, reflected in folklore. The relevance of the articleis to identify the importance of philosophical ideas in folklore and in their theoretical justification. Inthis regard, in the studies of folklore, taking into account the depth of philosophical thoughts, the mostimportant is the philosophical and ideological analysis of folk art.